A novel triazine-aryl-bis-indole derivative inhibits both phosphodiesterase IV and expression of cell adhesion molecules1. Issue 86 (18th September 2015) - Banerjee, Tanima; Kar, Dipak; Krishna, Palakodety Radha; Prabhakar, Sunchu; Nomula, Rajesh; Mallula, Venkata Satyanarayana; Ravindranath, Hajari; Sridhar, Gattu; Adepu, Ramesh; Srikanth, Gourishetty; Mabalirajan, Ulaganathan; Ghosh, Balaram; et al.
<x xml:space="preserve">Abstract</x> Triazine-aryl-bis-indole derivative inhibits phosphodiesterase activity.